The expression of ccn3 (nov) RNA and protein in the rat central nervous system is developmentally regulated. Issue 3 (1st June 2001) - Su, B-Y; Cai, W-Q; Zhang, C-G; Martinez, V; Lombet, A; Perbal, B
Abstract : Aims —To establish the expression pattern of ccn3 (nov) in the central nervous system (CNS) of adult rats and to determine whether spatiotemporal variations in the expression of ccn3 (nov) are related to specific developmental stages and/or specific CNS functions. Methods —The sites of ccn3 (nov) expression have been identified by in situ hybridisation using didoxigenin labelled cRNA and by the reverse transcription-polymerase chain reaction (RT-PCR). The rat CCN3 (NOV) protein was characterised by western blotting performed on brain extracts. The localisation of the CCN3 (NOV) protein in the brain was established by immunocytochemistry. Results —Increased expression of ccn3 (nov) was detected in the developing brain of rats after birth, as shown by RT-PCR and immunocytochemistry analysis performed on a series of samples taken between day 5 (P5) and day 300 (P300), with a pronounced peak between P15 and P150, suggesting that CCN3 (NOV) might play a role in the maintenance or establishment of specific brain functions. The relatively high amounts of an N-terminal truncated CCN3 (NOV) related protein detected both in the brain tissues and cerebrospinal fluid suggested that post translational processing of CCN3 (NOV) might be particularly prevalent in the brain. Such processing might be of biological importance in the light of the previously reported growth stimulatory effects of N-terminal truncated CCN3 (NOV) isoforms. Conclusions —The postnatal differential expression of ccn3 (nov) in the brain of developing rats suggests that CCN3 (NOV) might be involved in the acquisition of specific functions. The rat species provides an as yet unequalled system for these studies. Because the CCN3 (NOV) protein is detected in restricted areas of the brain, it will be interesting to establish whether variations of ccn3 (nov) expression are associated with normal cognitive processes and whether ccn3 (nov) expression is affected by aging. In addition, because CCN3 (NOV) is found in the spinal cord and along the axonal processes, it will be of interest to determine the expression of the normal and truncated isoforms of CCN3 (NOV) in various pathological conditions, such as neurodegenerative diseases.